Avaliação da eficácia do tratamento enzimático de biopolimento de tecido denim - Silva, Daniele Cardoso da (2021)
The growing demand from consumers and clothing manufacturers looking for highperformance fabrics has driven the development of finishes in the textile area. Studies aimed at the various types of finishing and fibers used in fabrics ensure higher quality. The biopolishing finish is an example of finishing, that is, the biopolishing process improves the properties of the article, ensuring greater durability to the product. In this work, the application of the biopolishing finish on denim fabrics was performed. The application process was carried out at a temperature of 60°C, for 45 min, with a 1:7 ratio (fabric mass: solution volume) in an all-in process, with product concentration of 0.7% and 1 .5% on the tissue mass. In order to verify the effectiveness of the enzymatic biopolishing finish, the application of the product on denim fabrics with compositions: T1-Fabric 1 (full cotton); T2-Fabric 2 (98% cotton 2% elastane) and T3-Fabric 3 (67% cotton 30% polyester 3% elastane). At the end of the experiments, improvements in the elongation parameters of the samples composed of spandex can be observed.